2011
DOI: 10.1136/injuryprev-2011-040135
|View full text |Cite
|
Sign up to set email alerts
|

Reducing regional inequality in mortality from road traffic injuries through enforcement of the mandatory motorcycle helmet law in Taiwan

Abstract: Background This study was conducted to examine whether passage of the mandatory motorcycle helmet law in 1997 reduced the regional inequality in mortality from road traffic injuries (RTIs) across 22 cities/counties in Taiwan. Methods We calculated the absolute (between-group variance, BGV) and relative (rate ratio between the city/ county with the highest and lowest rate, RR) terms of inequality for the overall and motorcycle-related RTI mortality rates, the rate of helmet use and three other explanatory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
(23 reference statements)
0
11
2
Order By: Relevance
“…By contrast with the great increase in helmet use rates (from 45% in 1997 to 92% in 2002) in years immediately after the helmet law was passed in 1997,6 we noted a mild decrease of helmet use rates in this study, from 92% in 2001 to 89% in 2009. Different indicators of socioeconomic position showed divergent changes in social equality in helmet use: urbanisation level and income level displayed a significant reduction of social inequality, yet education level showed a significant increase of social inequality.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…By contrast with the great increase in helmet use rates (from 45% in 1997 to 92% in 2002) in years immediately after the helmet law was passed in 1997,6 we noted a mild decrease of helmet use rates in this study, from 92% in 2001 to 89% in 2009. Different indicators of socioeconomic position showed divergent changes in social equality in helmet use: urbanisation level and income level displayed a significant reduction of social inequality, yet education level showed a significant increase of social inequality.…”
Section: Discussioncontrasting
confidence: 97%
“…With regard to the rigorousness of police ticketing non-helmet use, a previous study in Taiwan using the Police Traffic Accident Registry data indicated that relaxation of law enforcement by police in some counties resulted in a correspondingly greater decline of helmet use 6. A study in Thailand revealed high disparity in helmet use (from 36% in South region to 82% in Bangkok) and highly associated with regional conviction rate of motorcyclists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33,44,45 In Taiwan, China, for example, a 1997 law making helmet use mandatory has substantially lowered mortality from road traffic injury. 19,46 Furthermore, community interventions should concentrate on local environments and on raising public awareness surrounding safety and how to prevent injuries, especially among children and migrants. Education for injury prevention has given good results and is affordable in developing countries.…”
Section: Resultsmentioning
confidence: 99%